The Importance of Teacher Professionalism in Improving Learning Quality - Zaleha, Zaleha; Fitria, Happy; Wahidy, Achmad (Journal of Social Work and Science Education, 2022)
The purpose of this research is to identify and characterize the influence of teacher professionalism in increasing learning quality at SMP Negeri 2 Tanjung Lago in Banyuasin Regency. This is a qualitative research method using a descriptive approach. The following data gathering methods were used: (1) observation; (2) interviews; and (3) documentation. Techniques for analyzing research data include (1) data reduction, (2) data presentation, and (3) data verification/conclusion. According to the study's findings, the role of teacher professionalism in improving the quality of learning at SMP Negeri 2 Tanjung Lago, Banyuasin Regency can be described as active, with teachers planning ahead of time in preparing lesson plans, carrying out learning in accordance with the established curriculum, and referring to the Minister Regulation, where the educational process leads to a character approach using a contextual approach. Furthermore, every mid-semester, every semester, the instructor reviews the learning outcomes.